The South Sandwich Islands – a community of meta-populations across all trophic levels - Hart, T; Convey, P (Taylor and Francis, 2018)
The South Sandwich Islands are a relatively pristine volcanic archipelago in the Southern Ocean that experience high levels of natural disturbance. The archipelago spans the biological transition between the sub-Antarctic and maritime Antarctic. They host the southern boundary for some sub-Antarctic communities and the northern boundary for some maritime Antarctic communities. Vertebrate communities are dominated by Chinstrap and Macaroni penguins in the north and Adélie penguins in the south. Terrestrial plant and animal communities are less well differentiated; their distribution more influenced by the distribution of geothermally-warmed ground. We review current biodiversity knowledge, the influence of contemporary change on the archipelago, and their regional importance to Southern Ocean species. We pose questions on how to manage the islands in the contexts of climate change, fishing and human visitation. Climate change and fisheries will likely impact on the islands’ biota, but we conclude that introduced species pose the largest threat to biodiversity. Given the ephemeral nature of populations across all trophic levels, we suggest that the islands be managed as one unit rather than individually and we recommend practical changes to permitting and to increase the no-take zone in the existing Marine Protected Area to protect penguin foraging areas.